Sprawa wysłania okupacyjnych wojsk brytyjskich do Austrii Niemieckiej (1918-1919) - Jeziorny, Dariusz (Acta Universitatis Lodziensis. Folia Historica, 1999)
The armistice signed on 3rd November 1918 between the Entente and Austria-Hungary contained the clause giving the Allied troups the possibility of free movement through the territory (roads, railways and waterways) of the former Habsburg monarchy and the occupation of the most important strategic points to continue further war with Germany or to keep order. The British soldiers were regarded to be the best forces to participate in such military operations. The propositions of occupation of Vienna and other main places of German Austria were coming from different sides. The first request was announced by the French government. Marshal Foch, the main supporter of the military intervention in Vienna, wated the British troups gathered in southern Europe under the command of gen. Franchet d’Esperey to go to Budapest and Vienna. It was to be only „the march of glory” of the winners. But the French were going to eliminate Italian army from this expedition, because the real reason was to enlarge the French influence in Central Europe. However the British government, during their disscutions in November 1918, did not agree to send their troups. The second, very unclear proposition of the military intervention came from Austrian Foreign Office. Otto Bauer, the head of the foreign service of the newly bom republic, wanted to prevent The Yugoslav or Italian occupation of Carinthia. Yugoslavs and Italians, fighting against each other, were going to improve their strategic position and Austrian diplomacy intended to avoid such an issue. But no British soldier was sent to Klagenfurt and Villach. The British troups were asked once again to come to Vienna after the announcement the Soviet Republic in Hungary on 21st March 1919. The strong anti-socialist circles (the Catholics and the supporters of the ex-Emperor) demanded the expedition of the British soldiers to Austria to avoid the same solution there and to constrain the socialist power. But there were no British troups ready to go to Vienna in the nearest of this capital. It was the main reason of non-intervention politics of London Foreign Office. The British diplomats decided only to threaten the Austrian government to stop all food supplies in the case of communist coup d’etat. That argument allowed to keep order in Austria in April 1919. British government were very unwilling to send their troups to Austria. And that was one of the main reasons of lack of stability in Central Europe in the first months after the world war I.